Suprascapular neuropathy in volleyball players. Issue 3 (1st June 2000) - Witvrouw, E; Cools, A; Lysens, R; Cambier, D; Vanderstraeten, G; Victor, J; Sneyers, C; Walravens, M
Abstract : Background —Suprascapular nerve entrapment with isolated paralysis of the infraspinatus muscle is uncommon. However, this pathology has been reported in volleyball players. Despite a lack of scientific evidence, excessive strain on the nerve is often cited as a possible cause of this syndrome. Previous research has shown a close association between shoulder range of motion and strain on the suprascapular nerve. No clinical studies have so far been designed to examine the association between excessive shoulder mobility and the presence of this pathology. Aim —To study the possible association between the range of motion of the shoulder joint and the presence of suprascapular neuropathy by clinically examining the Belgian male volleyball team with respect to several parameters. Methods —An electromyographic investigation, a clinical shoulder examination, shoulder range of motion measurements, and an isokinetic concentric peak torque shoulder internal/external rotation strength test were performed in 16 professional players. Results —The electrodiagnostic study showed a severe suprascapular neuropathy in four players which affected only the infraspinatus muscle. In each of these four players, suprascapular nerve entrapment was present on the dominant side. Except for the hypotrophy of the infraspinatus muscle, no significant differences between the affected and non-affected players were observed on clinical examination. Significant differences between the affected and non-affected players were found for range of motion measurements of external rotation, horizontal flexion and forward flexion, and for flexion of the shoulder girdle (protraction); all were found to be higher in the affected players than the non-affected players. Conclusions —This study suggests an association between increased range of motion of the shoulder joint and the presence of isolated paralysis of the infraspinatus muscle in volleyball players. However, the small number of patients in this study prevents definite conclusions from being drawn.